(untitled) (Devenires, 2023)
In her debut novel, Como caracol... –winner of the prize Gran Angular 2018–, Alaíde Ventura Medina (Xalapa, 1985) explores the reunion of a girl with her maternal grandmother, who is transitioning into Alzheimer’s disease. Through the narration of the onset of the illness the author links the past with the affective, bodily, and symbolic present. The grandmother’s memory loss translates into a loss of self-esteem and self-identity, and into a deterioration of the physical and emotional wellbeing of the family. Nevertheless, self-pity and social discredit are replaced by the grandmother’s dignified proposal in the face of old age, illness, and death. Dependance on others and physical deterioration turn into the fear of losing autonomy and renders the individual fragile and a vulnerable both socially and psychologically. Yet Alzheimer’s also forces a reevaluation of family history: secrets are revealed, absences and resentments are explained. Thus, the illness brings about a new form of coexistence called “of affect” (Pons and Guerrero, 2018), to face old age, illness, and physical and emotional wear.